Development of lurik Bayat fabric design for interior elements - Agung Purnomo (Gelar : Jurnal Seni Budaya, 2023)
This scientific article investigates the evolution of Lurik Bayat fabric, traditionally confined to the clothing industry, aiming to expand its role in the creative industry and enhance community well-being. The research commences with a thorough examination of the current state of Lurik fabric in the Bayat Sub District, encompassing analysis of its design, production processes, and community utilization. In response to the demand for interior applications, a comprehensive mapping of new functions is executed. Data is collected through a multifaceted approach involving observation, literature study, interviews, and documentation, encompassing artifacts and informant perspectives. The design experiment employs a structured approach to formulate and compose Lurik Bayat fabric designs for diverse interior elements, including drapes (curtains), lampshades, table fabrics, pillowcases, and bed covers. The outcomes of this study unveil innovative designs geared towards benefiting Lurik fabric craftspersons and facilitating the integration of the fabric into diverse creative applications beyond its traditional role in clothing. The findings emphasize the potential of Lurik Bayat fabric to contribute to the broader creative industry and improve the overall well-being of the community. The comprehensive exploration of design, production, and application provides valuable insights for practitioners, researchers, and stakeholders interested in advancing the role of traditional fabrics in contemporary creative contexts.